Relationship between age and weight with the incidence of anemia in seko barat public health center - Irmayanti, Irmayanti; Yulianti. N; Devi Darwin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Anemia is a medical condition in which the number of red blood cells (erythrocytes) or hemoglobin levels in the blood are below normal. The phenomenon of anemia in remote areas such as Seko Barat can be explained by several main factors. According to Guyton and Hall (2016), limited access to health services in remote areas can hinder early detection and treatment of anemia. The type of research used is a Cross Sectional Study. The population in this study were pregnant women who were able to check themselves at the Seko Balralt Health Center. The population in this study was 34 people. The sample size used in this study used a total sampling technique, namely by taking all members of the population as samples. By testing using the chi-square technique, p = 0.013 is obtained, which is smaller than α = 0.05, this means that Ho is rejected and Ha is accepted. Thus, there is a relationship between body weight and the incidence of anemia at the Seko Barat Health Center, North Luwu Regency, South Sulawesi.